Implementing the 2017 EFP/AAP Periodontal Disease Classification in The Diagnosis and Management of Endo-Periodontal Lesions: A Case Report - Hock Siang Chua; Zhi Kuan Saw; Shahida Mohd-Said (FKG Universitas Syiah Kuala, 2024)
Endo-periodontal lesions (EPL), characterised by the involvement of both pulpal and periodontal tissues, present diagnostic and therapeutic challenges in dental practice. This case report highlights the successful management of an EPL in a 52-year-old female patient with the guidance of the 2017 EFP/AAP Classification. Tooth 43 was incidentally found to be necrotic with symptomatic apical periodontitis and was subsequently root canal treated. However, at 15 months post-obturation, the tooth was presented with acute periodontal swelling at the buccal gingiva with deep pockets, bleeding-on-probing, calculus deposition, and periapical radiolucency. Using the 2017 EFP/AAP Classification, the diagnosis of EPL without root damage in non-periodontitis patients with Grade III was made. This report facilitates better and more accurate diagnosis-making for effective EPL treatment outcomes.